2021
DOI: 10.3389/fpubh.2021.670669
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Characteristics and Management Measures of Sporadic COVID-19 Outbreaks From June 2020 to January 2021 in China: The Importance of Tracking Down “Patient Zero”

Abstract: There are occupational disparities in the risk of contracting COVID-19. Occupational characteristics and work addresses play key roles in tracking down “patient zero.” The present descriptive analysis for occupational characteristics and management measures of sporadic COVID-19 outbreaks from June to December 2020 in China offers important new information to the international community at this stage of the pandemic. These data suggest that Chinese measures including tracking down “patient zero,” launching mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…15 Epidemiological investigations revealed that the risk of imported epidemics in port cities was high, and high-risk occupations were more likely to be infected and cause the spread of the epidemic. 16 Since different COVID-19 vaccines have been marketed, countries around the world have formulated different vaccination strategies and priority is generally given to high-risk groups, such as medical workers and public service workers. 17 , 18 Thus, we chose different occupations who faced a higher risk of infection as the target population in this research.…”
Section: Discussionmentioning
confidence: 99%
“…15 Epidemiological investigations revealed that the risk of imported epidemics in port cities was high, and high-risk occupations were more likely to be infected and cause the spread of the epidemic. 16 Since different COVID-19 vaccines have been marketed, countries around the world have formulated different vaccination strategies and priority is generally given to high-risk groups, such as medical workers and public service workers. 17 , 18 Thus, we chose different occupations who faced a higher risk of infection as the target population in this research.…”
Section: Discussionmentioning
confidence: 99%
“…China had taken the extremely stringent comprehensive intervention measures named the zero-COVID-19 policy to prevent the transmission of SARS-CoV-2 after the initial outbreak of COVID-19 occurred in Wuhan city in early 2020 [ 13 , 14 ]. Therefore, during the first three years of the pandemic COVID-19, only sporadic clusters of COVID-19 cases occurred in a few cities in mainland China and the transmission of SARS-CoV-2 was interrupted within a few weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiology of coronavirus disease 2019 (COVID- 19), is transmitted through respiratory tract by inhaling the virus in droplets and aerosol. China had taken the extremely strict non-pharmaceutical interventions to contain SARS-CoV-2, called "zero-COVID-19 policy, " after recognition of the disastrous consequences of COVID-19 in early 2020 (1,2). The zero-COVID-19 policy played important roles in the control of COVID-19 in the mainland China.…”
Section: Introductionmentioning
confidence: 99%